Hair Tonic Formulation of Black Tea Extract (Camellia sinensis) as Hair Growth - Nurul Arfiyanti Yusuf; Besse Hardianti; Rahma Rahma (Journal of Fundamental and Applied Pharmaceutical Science, 2021)
Black tea contains flavonoid and its derivate which is a mechanism of actions to stimulate and increase cell proliferation of hair dermal papilla cell to suppress the production of tumor necrosis factor alpha (TNF alpha) that trigger baldness. This study aimed to determine the stable hair tonic formula and to investigate the effectiveness of black tea extract hair tonic in rabbits (oryctolagus cuniculus) as animal testing. There were 3 different concentrations used in this study namely formula 1 (1.25 % of black tea extract), formula 2 (2.5 % of black tea extract) and formula 3 (5 % of black tea extract). The physical stability evaluation was conducted using some tests such as organoleptic, pH, density determination and viscosity test. The result of this evaluation showed that all the three formulas were stable, its effectiveness as hair restorer then was tested and the result of this test indicated that black tea extract has activity as a hair fertilizer and the optimum extract was shown by the formula 3 with black tea extract concentration of 5% with the hair growth in the 18th day i.e., 9.62 ± 0.365 mm.